2020
DOI: 10.1080/17461391.2020.1775895
|View full text |Cite
|
Sign up to set email alerts
|

Fruit supplementation reduces indices of exercise‐induced muscle damage: a systematic review and meta‐analysis

Abstract: This systematic review and meta-analysis examined the effects of fruit supplements on indices of muscle damage and physical performance measures following muscle-damaging exercise protocols. The PEDro scale and Cochrane's risk of bias tool was used to critically appraise each study, whilst forest plots were generated to report on standardised mean differences (SMD) and p-values. The studies employed a crossover-randomised design, or a randomised controlled placebo design, with measures compared between the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 64 publications
(67 reference statements)
4
30
5
Order By: Relevance
“…This is the first review to evaluate the effects of dietary nitrate supplementation on EIMD and therefore direct comparisons with previous systematic reviews and metaanalyses are not possible. However, our findings for muscle soreness and muscle function recovery are broadly in line with a recent review of fruit supplements on EIMD (Doma et al 2021), which like nitrate based supplements, are purported to attenuate markers of EIMD via antioxidant and/or anti-inflammatory effects. These authors reported that supplements derived from fruit (poly)phenols accelerated the recovery of isometric strength and reduced muscle soreness following exercise.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is the first review to evaluate the effects of dietary nitrate supplementation on EIMD and therefore direct comparisons with previous systematic reviews and metaanalyses are not possible. However, our findings for muscle soreness and muscle function recovery are broadly in line with a recent review of fruit supplements on EIMD (Doma et al 2021), which like nitrate based supplements, are purported to attenuate markers of EIMD via antioxidant and/or anti-inflammatory effects. These authors reported that supplements derived from fruit (poly)phenols accelerated the recovery of isometric strength and reduced muscle soreness following exercise.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, except a possible increase of CRP 48 h post-exercise (SMD: 0.55), nitrate had no effect on other inflammatory markers (IL-8, IL-6, TNF-a). These disparate findings might be attributed to the fact that the analysis by Doma et al (2021) contained twice as many studies and thereby provided greater statistical power to detect effects compared to the present analysis. Indeed, the lack of effect of nitrate (in the form of beetroot juice) on the cytokines in the present analysis should be interpreted cautiously given only two studies measured these markers using differing experimental designs (Clifford, Bell et al 2016;Clifford, Allerton et al 2017).…”
Section: Discussionmentioning
confidence: 65%
“…In this sense, a systematic review and meta-analysis about the effects of antioxidants consumption showed that short-term polyphenol supplementation (e.g., quercetin) may boost athletic performance in predominately-trained males with an average intervention dose of 688 ± 478 mg·day −1 [ 105 ]. This has been reinforced by more recent research showing that acute and chronic supplementation with >1000 mg fruit-derived polyphenols per day will enhance recovery following muscle damage via antioxidant and anti-inflammatory mechanisms [ 106 ]; which suggest that fruit supplements could be used as part of the post-exercise recovery strategy although the need to educate and encourage athletes to consume more fruits and vegetables in the diet should be associated not only with recovery but also with health [ 107 ]. Similarly, curcumin is rich in polyphenols and has shown anti-inflammatory and antioxidant properties.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the available strategies, dietary interventions, particularly fruit, have gained considerable attention when it comes to improving recovery following EIMD (Doma et al 2021;Naderi et al 2018). Fruit could influence the recovery process because they contain (poly)phenols which could interact with the secondary cascade associated with EIMD, via their antioxidant and anti-inflammatory properties (Bowtell and Kelly 2019;Pereira Panza, Diefenthaeler, and da Silva 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all fruit is equal in terms of (poly)phenolic content and abundance and certain fruit might be more beneficial for exercise recovery. For example, in a simple meta-analysis of 25 studies of fruit on recovery from EIMD, berries were reported to have the greatest overall effect (Doma et al 2021). Berries are rich in anthocyanins (ACN), a subclass of (poly)phenols, responsible for the red-blue-purple pigmentation in fruits (Manach et al 2004;P erez-Jim enez et al 2010).…”
Section: Introductionmentioning
confidence: 99%